Pelatihan Pengolahan Sampah di Bank Sampah Koperasi Warga Sadaya (KOWASA) Kecamatan Jonggol Bogor Jawa Barat - Siagian, Irwan; Tambunan , Nurma; Bondan, Bondan; Nurul Aulia , Hanum (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2021)
Garbage is a living thing with human life, almost all human activities produce waste. This waste itself is generated from residents who are in the Sukasirna Village community. However, if the waste management is managed properly and properly by utilizing qualified resources, it will generate income for the manager. Waste management managed by the Waste Bank has not been maximized. Community service by providing counseling on how to manage waste, both organic and inorganic waste optimally so that the waste produced is not only a source of environmental problems but can generate income. .Solutions are given to service partners by conducting discussion activities by sharing information and asking questions about the problems they face boldly. The techniques used in community service are as follows: a, direct observation, namely visiting partner locations, b. carry out community service with an education system and question and answer regarding the management of organic waste and inorganic waste, c. provide skills in managing organic and inorganic waste, d. conduct and share together to find an agreement in waste management so that it does not become a problem for the environment. The output targets to be achieved in this service evaluation are as follows: a. people who have skills, b. product worthy of high price from waste raw materials.